VOLUME 2, NO 1 (2014) - Chief, Editor In (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2014)
You are now holding the 2nd issue of Aro the Scientific Journal of Koya University. Aro is a newly established journal with ambition to become a globally recognized scientific journal with wider local impact. The editorial team is determined to keep the path of such a mission and sustain Aro’s future publication. Aro was created with long-term visions of becoming accessible to all researchers in Kurdistan and beyond, and covering a wide range of scholarly disciplines in sciences. The focus of the journal is to reflect that of the Koya University, namely promoting scientific knowledge and research in Kurdistan. Aro aspires to become a channel for exchange of research by establishing academic connections between scholars. Aro is a journal of original scientific research, global news, and commentary. The Aro Scientific Journal is a peer-reviewed, open access journal that publishes original research articles as well as review articles in areas of natural sciences and engineering. In this issue you will have access to genuine research paper in variety of areas, such as biochemistry, engineering and material. Aro is a member of CrossRef, which is a not-for-profit membership association whose mission is to enable easy identification and use of trustworthy electronic content by promoting the cooperative development and application of a sustainable infrastructure. Beside its online publications, Aro has a semi-annual hard copy publication which is available free-of-charge. The warm response from researchers, academics and professionals made our task of creating an editorial Board a relatively easy one. It is clear that having a dedicated and well organized editorial board for the journal is only one side of the coin. The other is the ability to attract submissions of quality research and scholarly work. We are thankful to all of those who put their trust in Aro and presented their original research work for publication in the second issue of the journal, as well as, our thanks are extended to the eleven peer-reviewers from the universities worldwide for their efforts in reviewing Aro publications. Your support and feedback are invited and appreciated. Sincerely, Professor Khidir M. Hawrami Executive Publisher Dilan M. Rostam, Shwan K. Rachid, Salah I. Yahya, Sarkawt S. Abdulrahman Executive Editorial Board